Factors leading to the quality of family life and their relationship to resilience in the Corona crisis in Jeddah Governorate - Al-Malki, Hana Ali Aali (Journal of Humanities & Social Sciences, 2023)
Current search target to identify: Factors conducive to the quality of life and its relationship to the resilience of the Corona crisis, namely the factor (socio-economic, health-psychological). The descriptive approach was followed, and the sample consisted of (158) individuals recovering from the Coronavirus in Jeddah, and they were chosen in an intentional way, and the researcher prepared a questionnaire consisting of (40) statements, distributed on the factors (socio-economic-health-psychological). The results showed that the most prominent expressions of the social factor leading to the quality of family life and its relationship to resilience in the Corona crisis were represented in family cooperation that strengthens my resolve to confront the infection of the Corona crisis, the most prominent expressions of the economic factor leading to the quality of family life and its relationship to resilience in the Corona crisis represented in the easily overlooked Corona crisis because of the availability of treatment In government hospitals. also, it was found that there were no statistical differences at the level of (0.05) in the responses of the study sample members to the factor (economic, health, psychological) attributable to the heterosexual difference, and that there were statistical differences at the level of 0.05 in the responses of the study sample members to the factor (social) attributable to the gender difference in favor of females. And there were no statistical differences (0.05) in the responses of the study sample members to factors (socio-economic, health) attributable to different life variants, while statistical differences were found at (0.05) in the responses of the study sample members to the (psychological) factor due to different life variants in favor of groups older than 40. The study also established that there were no statistical differences at the level of 0.05 in the responses of the sample members to factors (social, health, psychological) attributable to the difference of the scientific qualification variable, and that there were statistical differences at the level of 0.05 in the responses of the sample members to the (economic) factor due to the difference of the scientific qualification variable in favor of the secondary qualification.